Fungal Taxonomy, Phylogeny, and Ecology A Themed Issue Dedicated to Academician Wen-Ying Zhuang - Gao, Cheng; Cai, Lei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are honored and privileged to edit this Special Issue, "Fungal Taxonomy, Phylogeny, and Ecology: A Themed Issue Dedicated to Academician Wen-Ying Zhuang". In this Special Issue, we are pleased to publish a comprehensive assemblage of 23 papers covering fungal taxonomy, phylogeny, and ecology, in which 76 new taxa from a broad taxonomic group and different ecological habitats are reported.